Bioceramic Resonance Effect on Meridian Channels: A Pilot Study. (6th July 2015) - Leung, Ting-Kai; Chan, Wing P.; Tai, Chen-Jei; Cho, Ting-Pin; Yang, Jen-Chang; Lee, Po-Tsung
Abstract : Bioceramic is a kind of material which emits nonionizing radiation and luminescence, induced by visible light. Bioceramic also facilitates the breakup of large clusters of water molecules by weakening hydrogen bonds. Hydrogen bond weakening, which allows water molecules to act in diverse ways under different conditions, is one of the key mechanisms underlying the effects of Bioceramic on biophysical and physical-chemical processes. Herein, we used sound to amplify the effect of Bioceramic and further developed an experimental device for use in humans. Thirteen patients who suffered from various chronic and acute illnesses that severely affected their sleep patterns and life quality were enrolled in a trial of Bioceramic resonance (i.e., rhythmic 100-dB sound waves with frequency set at 10 Hz) applied to the skin surface of the anterior chest. According to preliminary data, a "Propagated Sensation along Meridians" (PSM) was experienced in all Bioceramic resonance-treated patients but not in any of the nine control patients. The device was believed to enhance microcirculation through a series of biomolecular and physiological processes and to subject the specific meridian channels of Traditional Chinese Medicine (TCM) to coherent vibration. This noninvasive technique may offer an alternative to needle acupuncture and other traditional medical practices with clinical benefits.